Basic information on Afro-Asian countries - Afro-Asian Organization for Economic Co-operation.; Afro-Asian Organization for Economic Co-operation. (Cairo. Afro-Asian Organization for Economic Co-operation, 1962)
This book is a compilation of economic data concerning Afro-Asian countries which is continuously carried out by the Centre of the Afro-Asian Organization for Economic Co-operation.
rpm 22/01/2019
Loans
Keywords: Africa; Asia